DESIGN THINKING DALAM PEMBELAJARAN BERDIFERENSIASI BAHASA INDONESIA MAHASISWA PENDIDIKAN PROFESI GURU: design thinking, pembelajaran berdiferensiasi, bahasa Indonesia - Rustam Rustam; Oky Akbar; Ade Bayu Saputra (Jurnal Semantik, 2024)
The purpose of this study is to describe the application of design thinking in differentiated learning of content (material), process, and student learning products in Indonesian language learning in the Teacher Professional Education program. This research uses qualitative methods with case study studies. Data collection techniques through interviews and documentation studies while the participants are field experience students of the Teacher Professional Education (PPG) program in Jambi city high schools. The data analysis technique uses Milles & Huberman's interactive model, carried out with activities (during data collection), simplifying data (data reduction), presenting data (data display) and drawing conclusions (making conclusions). The results of the study illustrate that the competence of Indonesian language teachers is able to carry out differentiated learning using the design thinking approach through activities: (a) empathy treatment to form a maximum understanding of students (ermpathize), (b) formulate learning objectives with the concept of define, (c) formulate ideas in learning, (d) develop prototypes in learning, and (e) evaluate the teaching module. The implementation of differentiated learning involves interconnected, continuous, and interacting steps, forming a process that includes diagnostic assessment, curriculum analysis, evaluation of learner diagnostic results, and curriculum analysis.